Progress with Formalization in Medical Informatics? - van der Maas, Arnoud A.F. (American Medical Informatics Association, 2001)
The prevailing view of medical informatics as a primarily subservient discipline in health care is challenged. Developments in both general informatics and medical informatics are described to identify desirable properties of modeling languages and tools needed to solve key problems in the application field. For progress in medical informatics, it is considered essential to develop far more formal modeling languages, modeling techniques, and tools. A major aim of this development should be to expel ambiguity from concepts essential to medicine, positioning medical informatics “at the heart of health care.”